5x+6x-(8x+5)=

Simple and best practice solution for 5x+6x-(8x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6x-(8x+5)= equation:


Simplifying
5x + 6x + -1(8x + 5) = 0

Reorder the terms:
5x + 6x + -1(5 + 8x) = 0
5x + 6x + (5 * -1 + 8x * -1) = 0
5x + 6x + (-5 + -8x) = 0

Reorder the terms:
-5 + 5x + 6x + -8x = 0

Combine like terms: 5x + 6x = 11x
-5 + 11x + -8x = 0

Combine like terms: 11x + -8x = 3x
-5 + 3x = 0

Solving
-5 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 3x = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 3x = 0 + 5
3x = 0 + 5

Combine like terms: 0 + 5 = 5
3x = 5

Divide each side by '3'.
x = 1.666666667

Simplifying
x = 1.666666667

See similar equations:

| 3tgx=0 | | -3n+5=27 | | 19+8x-25=-7(3-x)+3x | | Senx=-1 | | tgx=0 | | w/2-30=53 | | y+5x-7=0 | | x+4/x-8 | | Y=(18+2x)/8 | | a^2/-3a-6 | | y/3=4 | | 4x^2+12x-7=9 | | n^2/-2n+8 | | 2x^2+25x-2000=0 | | n^2/-2n | | 9-3(x-2)=7+x | | 14/x=7/3 | | (18+2x)/8 | | 5/-8n | | 9x^3+35x^2-4x=0 | | y-3/y-1 | | b^2/7b+7 | | 30x+8x^2=0 | | 3(4+x)=x+16 | | 14/x=7/4 | | (1.1m-0.4)sq= | | a-6/a+2 | | -34+13x=13x-34 | | 5ab+9ab=-ab | | -5/2n | | 0.4(x-6)=4.4 | | 8x+8=6x+54 |

Equations solver categories